PEMBELAJARAN BAHASA INDONESIA BIDANG POLITIK DI MEDIA MASSA - Sutarsih NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Political terminology of Indonesian language is being in special space now and becomes a worrying thing to discuss in public areas. In its growing now, it is not only uses by the politician and the party on political space, but it is entering to public area and the general people. One of its caused is its application in mass media. Political terminology of Indonesian language in mass media will give political learning for the readers indirectly. The people can know and understand about political terminology of Indonesian language from mass media that they read.